Turnpike theorem for a class of set-valued mappings. (December 2019) - Zaslavski, Alexander J.
Abstract : In this work we study the asymptotic behavior of optimal trajectories for a class of superlinear mappings arising in economic dynamics. We establish the existence of an open everywhere dense subset F of the space of set-valued mappings such that each mapping fron F has the turnpike property.